Atherosclerosis: The Culprit and Co-victim of Vascular Dementia - Huang, Ya-Ting; Hong, Fen-Fang; Yang, Shu-Long (Frontiers in Neuroscience, 2021)
Vascular dementia (VD) is one of the significant factors that affect the quality of senectitude, which causes cognitive impairment only by cerebrovascular disease. Atherosclerosis (AS) is a chronic inflammatory syndrome and closely associated with VD. Analyzing the role of AS in VD will make a great contribution to its early detection and prevention, but their relationship has not been integrated into a complete network. This review summarizes AS biomarkers as VD predictors for the first time and describes the direct mechanisms of AS causing VD from five aspects-vascular morphogenesis, hemodynamic change, neurovascular unit damage (NVU), oxidative stress and microRNA(miRNA). Finally, it discriminates the relationship between AS and VD in common risk factors which can be disease or some molecules. In particular, these data implies that the role of AS in VD is not only a pathogenic factor but also a comorbidity in VD. This review aims to bring new ideas for the prediction and treatment of VD.